The Role of Akidah Akhlak Teacher Subjects in the Forming of Students' Characters - Aura Dzikri; Farilah Khairunnisa; Mutiara Mutiara; Rizka Abdillah (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This study aims to look at the roles and challenges faced by an educator in the formation of student character. The method used in this research is a literature review which is carried out using literature (library), either in the form of books, notes, or reports on the results of previous research. The results of this study indicate that teachers have complex tasks and responsibilities towards achieving educational goals, teachers are not only required to master the knowledge to be taught, have teaching knowledge and skills, teachers are also required to have morals, character and personality that can be used as role models. for students.